2020
DOI: 10.47577/tssj.v10i1.1216
|View full text |Cite
|
Sign up to set email alerts
|

A description of drug use among adolescents in Slovakia in different age and gender groups

Abstract: The paper describes the drug-using behaviour among young people (12-19 y.) within two age groups in Slovakia. The study aims to describe the prevalence of two different forms of drug-use (experimentation and use within the last 30 days) of legal and illegal substances: alcohol, nicotine (cigarettes), marijuana, and other illegal drugs. A descriptive analysis was applied to two age and gender groups. The research sample was made up of 2489 pupils in primary and secondary schools (various types) from different r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
0
0
Order By: Relevance
“…The Head of BNN also revealed that he prioritized saving Indonesia's young generation rather than legalizing cannabis [19] [20] [21]. Cannabis is one of the most abused substances by teenagers compared to other drugs [7] [22]. In addition, there is an increase in crime rates in certain countries that have legalized medical cannabis and there are alternative medicines other than the use of cannabis that can be used for medicinal purposes [23].…”
mentioning
confidence: 99%
“…The Head of BNN also revealed that he prioritized saving Indonesia's young generation rather than legalizing cannabis [19] [20] [21]. Cannabis is one of the most abused substances by teenagers compared to other drugs [7] [22]. In addition, there is an increase in crime rates in certain countries that have legalized medical cannabis and there are alternative medicines other than the use of cannabis that can be used for medicinal purposes [23].…”
mentioning
confidence: 99%